2014
DOI: 10.1159/000361021
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Artery Pulsatility Index Assessment at 11-13<sup>+6</sup> Weeks' Gestation

Abstract: Introduction: First-trimester uterine artery pulsatility index (PI) measurements form part of an algorithm used to assess the risk of developing pre-eclampsia. The objective of this study was to construct a population-specific reference range for both the lower and mean maternal uterine artery PI at 11-13+6 weeks' gestation and to assess measurement agreement. Materials and Methods: Reference ranges for mean and lower PI measurements were developed using polynomial regression models following prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…The participants of this study were a cohort from a larger study recruited between May 2011 and April 2012 for the purposes of construction of a reference range for uterine artery PI at 11-13 +6 weeks [16]. Women attending the unit for first trimester aneuploidy screening were assessed for eligibility and provided with information about the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The participants of this study were a cohort from a larger study recruited between May 2011 and April 2012 for the purposes of construction of a reference range for uterine artery PI at 11-13 +6 weeks [16]. Women attending the unit for first trimester aneuploidy screening were assessed for eligibility and provided with information about the study.…”
Section: Methodsmentioning
confidence: 99%
“…The inclusion and exclusion criteria for this study mirrored that of the larger study [16]. Women were eligible for inclusion if they had a singleton pregnancy with a CRL 45-84 mm on the day of the examination.…”
Section: Methodsmentioning
confidence: 99%
“…This finding is consistent with other studies. (16,17,18) Our study demonstrated lower resistance and high velocity flow in normal pregnancies than increased resistance and pulsatility index with pregnancies associated with complications. This reflects there are changes in the uteroplacental circulation in very early stage in pregnancies, which are going to get complicated.…”
Section: Discussionmentioning
confidence: 54%
“…These physiological changes convert the spiral arteries from narrow muscular vessels to wide non-muscular channels independent of maternal vasomotor control. In placental dysfunction there is impaired trophoblastic invasion of spiral arteries and this impairment is most marked in PE and IUGR [6,7]. Indirect evidence of impaired placental perfusion in pregnancies destined to develop PE and IUGR has been provided by Doppler studies of the uterine arteries which showed increased PI during both the second and also in the first trimester of pregnancy [8].…”
Section: Discussionmentioning
confidence: 99%